1994
DOI: 10.1128/mcb.14.2.1347-1354.1994
|View full text |Cite
|
Sign up to set email alerts
|

Polypurine Sequences within a Downstream Exon Function as a Splicing Enhancer

Abstract: We have previously shown that a purine-rich sequence located within exon M2 of the mouse immunoglobulin mu gene functions as a splicing enhancer, as judged by its ability to stimulate splicing of a distant upstream intron. This sequence element has been designated ERS (exon recognition sequence). In this study, we investigated the stimulatory effects of various ERS-like sequences, using the in vitro splicing system with HeLa cell nuclear extracts. Here, we show that purine-rich sequences of several natural exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Even in Saccharomyces cerevisiae , where there appears to be little or no alternative splicing and pyrimidine tracts are often unrecognizable, increasing the polypyrimidine content can increase the use of adjacent 3′ splice sites (Parker and Patterson, 1987; Patterson and Guthrie, 1991). Exon sequences have also been shown to act in combination with other splicing signals to increase the efficiency of splicing and enable greater regulation (Hoshijima et al ., 1991; Lavigueur et al ., 1993; Sun et al ., 1993; Watakabe et al ., 1993; Xu et al ., 1993; Tanaka et al ., 1994; Tian and Maniatis, 1994; Humphrey et al ., 1995). Generally, these so‐called splicing enhancer elements are purine rich, but non‐purine‐rich sequences have also been shown to act as splicing enhancers (Staknis and Reed, 1994; Tian and Kole, 1995; Coulter et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Even in Saccharomyces cerevisiae , where there appears to be little or no alternative splicing and pyrimidine tracts are often unrecognizable, increasing the polypyrimidine content can increase the use of adjacent 3′ splice sites (Parker and Patterson, 1987; Patterson and Guthrie, 1991). Exon sequences have also been shown to act in combination with other splicing signals to increase the efficiency of splicing and enable greater regulation (Hoshijima et al ., 1991; Lavigueur et al ., 1993; Sun et al ., 1993; Watakabe et al ., 1993; Xu et al ., 1993; Tanaka et al ., 1994; Tian and Maniatis, 1994; Humphrey et al ., 1995). Generally, these so‐called splicing enhancer elements are purine rich, but non‐purine‐rich sequences have also been shown to act as splicing enhancers (Staknis and Reed, 1994; Tian and Kole, 1995; Coulter et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been shown that the selection of a splice site depends not only on its own sequence but also on the context around that sequence (28). Regarding this point, exons that are intrinsically poor splicing substrates, because of small size or weak flanking splice sites, have been proposed to contain positive-acting splicing elements, referred to as exonsplicing enhancers (17,42,48). Canonical exon-splicing enhancer sequences were, however, not easily identifiable in the 147-bp cassette-exon region.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, if purine content is the major factor, replacement of one purine-rich enhancer sequence of a certain length with another equally purine-rich sequence of the same length should result in similar splicing outcomes. But again, this is not the case (47). These examples highlight the importance of specific sequences, in addition to purinecontent, in defining enhancer elements.…”
Section: Enhancer Structure and Functionmentioning
confidence: 99%
“…Exonic enhancers direct U2AF and U2 binding to the 3′ splice site and U1 binding to the 5′ splice site, respectively. For bona fide enhancers it appears that the specific sequence is more important than the overall purine content (47). If the purine content was a more important variable than the specific sequence, then changes to the sequence that do not affect purine content would be expected to have no consequence.…”
Section: Enhancer Structure and Functionmentioning
confidence: 99%